Rapid Detection of Dendritic Cell and Monocyte Disorders Using CD4 as a Lineage Marker of the Human Peripheral Blood Antigen-Presenting Cell Compartment - Jardine, Laura; Barge, Dawn; Ames-Draycott, Ashley; Pagan, Sarah; Cookson, Sharon; Spickett, Gavin; Haniffa, Muzlifah; Collin, Matthew; Bigley, Venetia (Frontiers in Immunology, 2013)
Dendritic cells (DCs) and monocytes are critical regulators and effectors of innate and adaptive immune responses. Monocyte expansion has been described in many pathological states while monocyte and DC deficiency syndromes are relatively recent additions to the catalogue of human primary immunodeficiency disorders. Clinically applicable screening tests to diagnose and monitor these conditions are lacking. Conventional strategies for identifying human DCs and monocytes have been based on the use of a lineage gate to exclude lymphocytes, thus preventing simultaneous detection of DCs, monocytes and lymphocyte subsets. Here we demonstrate that CD4 is a reliable lineage marker for the human peripheral blood antigen presenting cell compartment that can be used to identify DCs and monocytes in parallel with lymphocytes. Based on this principle, simple modification of a standard lymphocyte phenotyping assay permits simultaneous enumeration of four lymphocyte and five DC/monocyte populations from a single sample. This approach is applicable to clinical samples and facilitates the diagnosis of DC and monocyte disorders in a wide range of clinical settings, including genetic deficiency, neoplasia and inflammation.